Evaluation of spermatozoa DNA tests for an assisted reproductive techniques (ART) program : correlation with semen parameters and ART outcome - Burger, Riana (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)--Stellenbosch University, 2013.